In silico study of secondary metabolites of Borneo endemic plant Shorea brunnescens as an anti-cancer drug candidate - Andifa Anugerah Putra; Huwaida, Nisriana Najla; Takarini, Rinta Dwi; Nur’ain, Rizka (Generasi Biologi Indonesia, 2023)
Borneo Island is one of the greenest islands in the world has thousands of endemic plants. Unfortunately, many of these plants are in endangered status. One of the endemic endangered plants from Borneo is Shorea brunnescens or locally named Selangan Batu Tinteng. Based on research, the bark of Shorea brunnescens contains the compound e-viniferin, which is recorded in the literature as an anti-cancer compound, especially breast cancer. The anti-cancer potential of Shorea brunnescens could be a driving force for conservation and protection of the plant, which has never been done before. Therefore, further research is needed regarding the effectiveness and capacity of Shorea brunnescens as an anti-cancer medicinal material. This study aims to examine the potential success rate of the anti-cancer properties of Shorea brunnescens through molecular docking of the compound e-viniferin against the proteotype of the main enzyme of breast cancer cells, Cytochrome P450. The method used was in silico modeling using PyRx and Discovery Studio software. First, screening of analog compounds through PubChem database (http://pubchem.ncbi.nlm.nih.gov/) based on Lipinski's rule, and obtained the three best analogs which will then be used as comparison ligands for docking simulation with Cytochrome P450 (CYP) receptors. The results obtained were that e-viniferin in Shorea brunnescens as the test ligand had the smallest affinity compared to the comparison ligand, which was -9.2 kcal/mol. It was concluded that Shorea brunnescens is able to inhibit cancer cells very well, so it has the potential to be developed as an anti-cancer drug candidate.